Nanocomposites for disinfection of drinking water ; toward point-of-use water treatment systems - Yoosefi Booshehri, Amin (2015)
The ever increasing standards for providing clean water have put more stress on water disinfection and decontamination technologies. Besides the higher standards, population growth, lack of infrastructures and distribution issues are the other main sources of stress. To address these issues, reliable methods of water treatment are needed that can be used in the decentralized systems. Advances in fabrication and engineering of nanomaterials have opened a new horizon in water treatment systems, especially with a point-of-use applicability and decentralization. Using nanomaterial, unlike traditional methods of water disinfection does not introduce any other secondary contamination and they can also be used in different scales. But the nanoparticles are needed to be removed from the treated water effectively and completely or not release to the water in the first place by being anchored on a support. In this study we focus on development of nanocomposite materials that can be used in point-of-use systems for water disinfection. Firstly, well dispersed silver deposited multiwall carbon nanotubes were produced. The nanocomposite was then attached on the surface of the hollow fiber membrane by simple method of filtration. This method of deposition of the nanocomposite has a couple of advantages over other chemical methods used in previous studies. Firstly, the structure and composition of the membrane remains intact. Secondly, after depletion of silver in the nanocomposite, it can be detached very easily and regenerated. Secondly, in view that silver is a noble and relatively expensive material and also the strict regulations on its release to the environment, copper oxide applicability was studied to substitute silver. In this part, CuO nanoleaves were produced and deposited on different substrates to be a simple and reliable means of water disinfection. In the first two parts of this study, leached metal ions are the first cause of disinfection. But in the third part, system was improved for better water quality without any metallic ions by using photocatalytic process. In this part silver deposited bismuth vanadate was used as the photocatalyst. The nanocomposite was used in a suspension and its antibacterial activity was studied under visible light irradiation. And finally in the last part of this study, photocatalytic polymer composite was fabricated by dispersing the photocatalyst in the polymer matrix. The resulted composite sheet showed a promising antibacterial activity for water treatment. In summary this thesis is devoted to development of low cost, reliable, efficient and stable water treatment system with a point-of-use applicability.